Strain‐Induced Ferroelectric Phase Transition in Group‐V Monolayer Black Phosphorus. Issue 4 (22nd February 2023) - Xu, Wen; Zheng, Jun‐Ding; Tong, Wen‐Yi; Wang, Jiu‐Long; Shao, Ya‐Ping; Zhang, Yu‐Ke; Tan, Yi‐Fan; Duan, Chun‐Gang
Abstract: Recently, a variety of elemental ferroelectric materials have been predicted in group‐V monolayers. However, black phosphorus, as a well‐known group‐V system with the similar structure, seems to be absent of spontaneous ferroelectric polarization. Based on first‐principles calculations, ferroelectric phase in monolayer black phosphorus (BP) is successfully obtained by strain engineering and the driving force can be attributed to Jahn–Teller effect. In addition, the bandgap of the monolayer BP is found to be tunable with applied strain, which can be adjusted to even achieve the metal polarization states. The work not only provides a new route to explore elemental ferroelectricity in 2D materials, but also suggests strain engineering as a powerful tool in related research. Abstract : Based on first‐principles calculations, ferroelectric phase in monolayer black phosphorus (BP) is successfully obtained by strain engineering and the driving force can be attributed to Jahn‐Teller effect. In addition, the band gap of the monolayer BP is found to be tunable with applied strain, which can be adjusted to even achieve the metal polarization states.